2007
DOI: 10.1099/vir.0.82284-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequence and analysis of the ovine herpesvirus 2 genome

Abstract: Ovine herpesvirus 2 (OvHV-2) is endemic in sheep populations worldwide and causes malignant catarrhal fever (MCF), a lymphoproliferative disease, in cattle, bison and deer. OvHV-2 has been placed in the gammaherpesvirus subfamily and is related closely to Alcelaphine herpesvirus 1 (AlHV-1). Here, the cloning, sequencing and analysis of the complete OvHV-2 genome derived from a lymphoblastoid cell line from an affected cow (BJ1035) are reported. The unique portion of the genome consists of 130 930 bp, with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 63 publications
1
89
1
4
Order By: Relevance
“…56,66 The genomes of OvHV-2 and AlHV-1 have been sequenced and compared. 30,33,41,138 The products of several open reading frames (ORFs) are used in transmission studies to establish whether latent or lytic infection patterns predominate in animals following challenge at different time points. 21,23,57,59,85,99,123 Expression in tissue of specific viral genes (in the case of OvHV-2, these include ORF9, DNA polymerase; ORF25, major capsid protein; ORF50, R-transactivator inducing latent to productive cycle switch; and ORF73, latency-associated nuclear antigen [LANA] homolog [genome maintenance protein]) is used to establish when productive infection occurs in the course of experimental infection.…”
Section: Ovine Herpesvirus-2 and The Mcf Virus Groupmentioning
confidence: 99%
“…56,66 The genomes of OvHV-2 and AlHV-1 have been sequenced and compared. 30,33,41,138 The products of several open reading frames (ORFs) are used in transmission studies to establish whether latent or lytic infection patterns predominate in animals following challenge at different time points. 21,23,57,59,85,99,123 Expression in tissue of specific viral genes (in the case of OvHV-2, these include ORF9, DNA polymerase; ORF25, major capsid protein; ORF50, R-transactivator inducing latent to productive cycle switch; and ORF73, latency-associated nuclear antigen [LANA] homolog [genome maintenance protein]) is used to establish when productive infection occurs in the course of experimental infection.…”
Section: Ovine Herpesvirus-2 and The Mcf Virus Groupmentioning
confidence: 99%
“…Identification of the OvHV-2 IL-10 gene During DNA sequencing of the complete OvHV-2 genome (Hart et al, 2007), analysis of the non-coding regions between open reading frames (ORFs) using the BLASTX algorithm (Altschul et al, 1990) identified a putative gene near the left terminus of the unique portion of the genome, termed Ov2.5. This had the potential to encode a homologue of other IL-10 molecules (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These M r correspond well, after accounting for the 36HA tag (3 kDa), with those predicted from sequence analysis for the nascent and mature forms of OvHV IL-10. To account for the presence in the supernatant of proteins derived from lysed cells, HEK 293T cells were transfected with pVR1255 containing an HA-tagged cDNA of the OvHV-2 Ov2 gene (Hart et al, 2007), the product of which is known to have an M r of 40 000 on SDS-PAGE gels and a nuclear/ cytoplasmic distribution. An Ov2-HA product was contained only in the cell pellet.…”
Section: Characterization Of the Ovhv Il-10 Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The viral DNA was detected in all 30 samples examined with a mean copy number of 3.124 Ă‚ 10 6 per 500 ng of tissue DNA ranging from $300 to 3 Ă‚ 10 7 copies ( (Hart et al, 2007). ORF73 codes for a homolog of the gammaherpesvirus latency-associated nuclear protein, which is involved in viral genome maintenance and expressed during lytic and latent infection (Ahn et al, 2002;Gailbreath et al, 2008;Hart et al, 2007).…”
Section: Ovhv-2 Dna and Transcripts Detected In Rabbits With Ovhv-2 Imentioning
confidence: 99%